Integrated bulk and single-cell RNA-sequencing identified disease-relevant monocytes and a gene network module underlying systemic sclerosis. Issue 116 (January 2021) - Kobayashi, Satomi; Nagafuchi, Yasuo; Okubo, Mai; Sugimori, Yusuke; Shirai, Harumi; Hatano, Hiroaki; Junko, Maeda; Yanaoka, Haruyuki; Takeshima, Yusuke; Ota, Mineto; Iwasaki, Yukiko; Sumitomo, Shuji; et al.
Abstract: Objective: Immunological disturbances have been reported in systemic sclerosis (SSc). This study assessed the transcriptome disturbances in immune cell subsets in SSc and characterized a disease-related gene network module and immune cell cluster at single cell resolution. Methods: Twenty-one Japanese SSc patients were enrolled and compared with 13 age- and sex-matched healthy controls (HC). Nineteen peripheral blood immune cell subsets were sorted by flow cytometry and bulk RNA-seq analysis was performed for each. Differential expression and pathway analyses were conducted. Iterative weighted gene correlation network analysis (iWGCNA) of each subset revealed clustered co-expressed gene network modules. Random forest analysis prioritized a disease-related gene module. Single cell RNA-seq analysis of 878 monocytes was integrated with bulk RNA-seq analysis and with a public database for single cell RNA-seq analysis of SSc patients. Results: Inflammatory pathway genes were differentially expressed in widespread immune cell subsets of SSc. An inflammatory gene module from CD16 + monocytes, which included KLF10, PLAUR, JUNB and JUND, showed the greatest discrimination between SSc and HC. One of the clusters of SSc monocytes identified by single-cell RNA-seq analysis characteristically expressed these inflammatory co-expressed genes and was similar to lung infiltrating FCN1 hi monocytes expressing IL1B . Conclusions: Our integrated analysis of bulk and single cell RNA-seq analysis identified an inflammatory gene module and a cluster of monocytes that are relevant to SSc pathophysiology. They could serve as candidate novel therapeutic targets in SSc. Highlights: An inflammatory gene module of CD16 + monocytes discriminated systemic sclerosis. A clusters of SSc monocytes characteristically expressed these co-expressed genes. They were similar to lung infiltrating FCN1 hi monocytes expressing IL1B. The gene module and monocytes could serve as novel therapeutic targets.